2005
DOI: 10.1063/1.1922570
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for pinpointing the best glass-forming alloys

Abstract: We present a model for the glass forming ability (GFA), based on phase selection of the glass over all the competing crystalline phases. Our analysis indicates that the best glass-forming zone can be either symmetric, or asymmetric, about the eutectic composition. Based on the model predictions we outline a microstructure-based strategy to pinpoint the off-eutectic composition with the optimum GFA. The practical implementation and significance of the strategy is demonstrated by discovering bulk metallic glasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 13 publications
1
69
0
Order By: Relevance
“…Ma et al demonstrated a glass whose melt could be easily vitrified because its composition was close to eutectic composition. 22) It is reasonable to consider that non-stoichiometric compositions cause decrease in the liquidus temperature and lead to decrease in the degree of supercooling. Subsequently, the decrease in the degree of supercooling increases the free energy of nucleation and suppresses the nucleation.…”
Section: Origin Of Preferential Surface Crystallizationmentioning
confidence: 99%
“…Ma et al demonstrated a glass whose melt could be easily vitrified because its composition was close to eutectic composition. 22) It is reasonable to consider that non-stoichiometric compositions cause decrease in the liquidus temperature and lead to decrease in the degree of supercooling. Subsequently, the decrease in the degree of supercooling increases the free energy of nucleation and suppresses the nucleation.…”
Section: Origin Of Preferential Surface Crystallizationmentioning
confidence: 99%
“…It is important to notice, however, that the precision of such approach will depend on the available information concerning the crystalline phases in each system (number and identity of such phases); the more information we have the narrower the > 0:1 areas can be. Figure 3 indicates the compositions of bulk samples reported in the literature [13][14][15][16][17][18][19][20] in a special region of the ternary Cu-Zr-Al system (30 to 75% Cu in the Zr-Cu line). Also indicated in this figure are the corresponding maximum sample diameters for each composition and we can observe nice correlation of the > 0:1 regions with the successful experiments to produce bulk glasses.…”
Section: Resultsmentioning
confidence: 99%
“…3 Compositions of bulk samples reported in the literature [13][14][15][16][17][18][19][20] in a special region of ternary system (30 to 75% Cu in the Zr-Cu line). …”
Section: Cu Zrmentioning
confidence: 99%
“…Good glass-forming compositions in a given system are often at or near ''deep'' eutectics, as has been clearly demonstrated in many alloy systems. [1][2][3][4][5][6][7][8] For binary systems, it is straightforward to use the eutectic compositions as starting points to explore novel metallic glasses because their phase diagrams are readily available. For multicomponent systems, however, it is hard to determine whether they have deep eutectics and where these deep eutectics are located.…”
Section: Introductionmentioning
confidence: 99%